Visual Arts As The Medium Of Dakwah From Islamic Perspective - Anwar ِ, Huda A . (2011)
Visual art is a form of artistic works that can be visualised by others in various form such acting in theater or film, drawing, curving, photoghraf and others. Under the situation of mind struggle which the whole world lives nowadays, the visual arts represent the most dangerous weapon ever known. The relationship between Islam and the art goes even further than the situation of the doctrinal clash about what is legal ( Halal ) and what is illegal ( Haram ) in art cases which goes into the area of the most necessary as the capacity of art to explain God’s calling upon spirits.